Boulders as building blocks: improving habitat and river connectivity for stream fish. Issue 4 (27th June 2012) - Branco, Paulo; Boavida, Isabel; Santos, José Maria; Pinheiro, António; Ferreira, Maria Teresa; Blanckaert, Koen; Garcia, Xavier‐François; Steiger, Johannes; Uijttewaal, Wim
ABSTRACT Fragmentation of freshwater systems is one of the more common human‐induced impacts on the environment, and one of the most dramatic because it leads to disconnections among riverine habitats, severely affecting fish populations. To counter this form of ecological abuse, there has been a significant increase of the number of restoration actions. This work approached stream restoration from a holistic point of view, combining habitat modelling with laboratory experimental research. A 2D hydrodynamic model was used to test the increase in weighted usable area (WUA) created by different boulder placement (BP) scenarios in a disturbed site, with a widespread potamodromous cyprinid fish – the Iberian barbel (Luciobarbus bocagei) – as the target species. This was complemented by experimental trials in a full‐scale experimental fishway with different bottom substrata arrangements, in order to assess the effects of boulders on barbel movements. Results show that instream BP increases WUA for barbel and facilitates fishway negotiation. The findings reflect the importance of placing instream boulders in fragmented systems in order to enhance suitable habitat area and river connectivity. However, BP must be specifically designed for each case and should always be preceded by a comprehensive study for each site and target fish species. Copyright © 2012 John Wiley & Sons, Ltd.